Uncover the Offensive Side of Disparagement Humor: An fMRI Study - Bartolo, Angela; Ballotta, Daniela; Nocetti, Luca; Baraldi, Patrizia; Nichelli, Paolo Frigio; Benuzzi, Francesca (Frontiers in Psychology, 2021)
Disparagement humor is a kind of humor that denigrates, belittles an individual or a social group. In the aim to unveil the offensive side of these kinds of jokes, we have run an event-related fMRI study asking 30 healthy volunteers to judge the level of fun of a series of verbal stimuli that ended with a sentence that was socially inappropriate but funny (disparagement joke -DJ), socially inappropriate but not funny (SI) or neutral (N). Behavioral results showed disparagement jokes are perceived as funny and at the same time offensive. However, the level of offense in DJ is lower than that registered in SI stimuli. Functional data showed that DJ activated the insula, the SMA, the precuneus, the ACC, the dorsal striatum (the caudate nucleus), and the thalamus. These activations suggest that in DJ a feeling of mirth (and/or a desire to laugh) derived from the joke (e.g., SMA and precuneus) and the perception of the jokes’ social inappropriateness (e.g., ACC and insula) coexist. Furthermore, DJ and SI share a common network related to mentalizing and to the processing of negative feelings, namely the medial prefrontal cortex, the putamen and the right thalamus.